1961
DOI: 10.1126/science.134.3485.1073
|View full text |Cite
|
Sign up to set email alerts
|

Immunization to Schistosoma mansoni in Mice Inoculated with Radiated Cercariae

Abstract: Preliminary experiments indicate that mice inoculated with cercariae of Schistosoma mansoni that have been exposed to cobalt-60 radiation in the range of 2500 to 3000 rep develop immunity to reinfection with nonradiated cercariae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

1962
1962
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…However, none of them has been able so far to give a consistent induction of more than 40% protection. The studies of testing irradiation-attenuated cercariae as a possible vaccine against schistosomiasis were performed more than 50 years ago (Villella et al 1961;Szumlewicz and Olivier 1963). Many studies have shown that administration of live irradiation-attenuated cercariae to a large range of laboratory animals Shi et al 1990Shi et al , 1993, including nonhuman primates (Shi et al 1993;Eberl et al 2000;Torben and Hailu 2007), could provide 70-90% protection against experimental S. mansoni and Schistosoma japonicum infections.…”
Section: Introductionmentioning
confidence: 99%
“…However, none of them has been able so far to give a consistent induction of more than 40% protection. The studies of testing irradiation-attenuated cercariae as a possible vaccine against schistosomiasis were performed more than 50 years ago (Villella et al 1961;Szumlewicz and Olivier 1963). Many studies have shown that administration of live irradiation-attenuated cercariae to a large range of laboratory animals Shi et al 1990Shi et al , 1993, including nonhuman primates (Shi et al 1993;Eberl et al 2000;Torben and Hailu 2007), could provide 70-90% protection against experimental S. mansoni and Schistosoma japonicum infections.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of schistosomes, doses of 3-4 krad of X-or c-radiation were shown to prevent developing schistosome worms surviving to the adult pathogenic egg-laying stage while doses of 1-3 krad resulted in persistence of a small proportion of stunted and generally sterile adults (Smithers, 1962). There followed various protection studies against S. mansoni and S. japonicum in mice and repeatedly exposed rhesus monkeys using cercariae exposed to relatively low levels of radiation (Hsu et al 1962 ;Radke and Sadun, 1963 ;Sadun et al 1964 ;Smithers, 1962 ;Villella et al 1961) and most studies reported higher levels of partial protection to challenge with very low doses of radiation which allowed a small proportion of stunted worms to survive. These studies were carried out at a time when the prevailing notion, based on studies in rhesus monkeys harbouring unattenuated S. mansoni infections Terry, 1965, 1967), was that the adult worm is the prime stimulus to protection and that the schistosomula stages contribute little to the development of resistance.…”
Section: R R a D I A T E D V A C C I N E S -E S T A B L I S H M E Nmentioning
confidence: 99%
“…Since the very first results from mice immunized with attenuated Schistosoma mansoni cercariae [22], where high levels of protection were observed, the search for an anti-schistosomiasis vaccine has turned out to be a huge challenge as those results has revealed difficult to be reproduced using individual antigens, even in the presence of strong adjuvants.…”
Section: Discussionmentioning
confidence: 99%